2022
DOI: 10.3390/ijerph19031675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Muscle Strength with Non-Alcoholic Fatty Liver Disease in Korean Adults

Abstract: Sarcopenia is known to be associated with non-alcoholic fatty liver disease (NAFLD). However, few studies have revealed the association between muscle strength and prevalence of NAFLD. We investigated the association by using relative handgrip strength in a nationwide cross-sectional survey. The participants were recruited from the Korean National Health and Nutrition Examination Surveys (KNHANES). A total of 27,531 subjects from the KNHANES were selected in our study. We used normalized handgrip strength, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Emerging studies have explored the relationships between skeletal muscle mass and NAFLD, hepatic steatosis, as well as significant liver fibrosis (8, 9, 20-23). However, most of them used less accurate surrogate measures, such as handgrip strength (8,9,22) and fatty liver index (23). Leveraging data from the Korean National Health and Nutrition Examination Surveys (KNHANES), Lee Sung-Bum found that handgrip strength was inversely associated with HSI, and the prevalence of NAFLD defined by HSI decreased in the quartile groups of handgrip strength (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging studies have explored the relationships between skeletal muscle mass and NAFLD, hepatic steatosis, as well as significant liver fibrosis (8, 9, 20-23). However, most of them used less accurate surrogate measures, such as handgrip strength (8,9,22) and fatty liver index (23). Leveraging data from the Korean National Health and Nutrition Examination Surveys (KNHANES), Lee Sung-Bum found that handgrip strength was inversely associated with HSI, and the prevalence of NAFLD defined by HSI decreased in the quartile groups of handgrip strength (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them used less accurate surrogate measures, such as handgrip strength (8,9,22) and fatty liver index (23). Leveraging data from the Korean National Health and Nutrition Examination Surveys (KNHANES), Lee Sung-Bum found that handgrip strength was inversely associated with HSI, and the prevalence of NAFLD defined by HSI decreased in the quartile groups of handgrip strength (9). Being partially consistent with our results, they also observed that the risk for NAFLD in females (OR[95%CI]: 0.30 [0.22-0.40]) was more relevant to muscle strength than that in males MAFLD, metabolic dysfunction-associated fatty liver disease; SMI, skeletal muscle mass index; OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten articles were included in this analysis (Figure 1) (9,(24)(25)(26)(27)(28)(29)(30)(31)(32). The selected studies involved 76,676 participants.…”
Section: Eligible Studies and Individual Characteristicsmentioning
confidence: 99%
“…Handgrip strength is an inexpensive and simple assessment tool to measure muscle strength and is suitable for the diagnosis of sarcopenia [ 7 ]. Previous studies found handgrip strength to be a predictor of non-alcoholic fatty liver disease and healthy aging [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%